EFFECT OF GIVING SILVER BLACK PLASTIC MULCH ON 14 GENOTICS OF LONG BEANS (Vigna sesquipedalis) - Taufan Rahmadi Aji (Institute of Computer Science (IOCS), 2022)
Study this aim for knowing influence gift mulch plastic black silver on results and component results plant peanut long. hypothesis which filed that is there is influence gift mulch plastic black silver on the yield and yield components of long bean plants. Study this implemented in the garden test University Brawijaya which located in the village of Jatikerto. Located at an altitude of ± 330 m above sea level, with Alfisol soil type. This research was conducted in February May 2008. This research uses Draft Plot Divided (RPT) with plot main use mulch and child plot form genotype peanut long. Ma s ing each repeated 3 time. As for treatment that is TM = without mulch, M = with mulch , G1 until G14 = genotype peanut long. Variable which observed that is: Age flowering, Age harvest, Long pod, Amount pod planting, Weight pod planting, Amount seed per pod, Amount pod planting, Amount clusters planting, Potency results planting, Amount pod percluster. Data which obtained analyzed with use analysis variety and done test F on level 5%. If results testing show results which different real, then proceed with the BNT test at the level of 5%. Results study show that interaction real on use mulch plastic black silver to 14 genotype peanut long occur on variable total flower planting, total pod per cluster, total cluster planting. Significant interaction on the yield of long bean plants on the use of mulch seen on weight pod planting and weight pod plot. kindly whole, plant peanut long which planted with use Plastic mulch gives higher yields.